The Impact of Digital Technologies, Including Artificial Intelligence on Teaching Roles in Further Education Colleges and Skills Sector in the UK - Fathulla, Kawa Abbas (Digital Repository of Theses, 2026)
Artificial intelligence (AI) and digital learning technologies are becoming increasingly embedded within the UK Further Education (FE) sector, reshaping teaching, learning and institutional practice. As FE colleges respond to government expectations for a digitally skilled workforce and a “modern Britain,” they face growing pressure to integrate AI in ways that improve learning while also navigating significant cultural, pedagogical and ethical challenges. This research explores the impact of AI on FE students’ learning experiences and examines the complexity of FE teachers’ viewpoints regarding digital and AI-enabled teaching technologies. This study aims to critically examine how artificial intelligence is viewed and experienced by teaching staff within the UK’s FE college sector. The study explores how AI is influencing teaching pedagogy and workforce readiness in a sector already facing many financial challenges and tasked with delivering the UK’s skills for industry. The study is grounded in a critical realist philosophy and employs Q methodology to systematically capture and analyse the subjective viewpoints of FE practitioners. Q methodology enabled the identification of shared perspectives across trainers and trainee trainers, highlighting points of consensus and divergence on the benefits, risks, and long-term implications of AI for vocational education. The research combined Q-sorts with semi-structured interviews and surveys to triangulate findings, ensuring robustness and validity. Ethical implications emerged strongly, with participants expressing concerns around privacy, data protection, transparency, accountability and fairness. These ethical issues can significantly influence learning quality, student wellbeing, autonomy and equity, highlighting the need for thoughtful and responsible AI implementation. The results reveal distinct clusters of perspectives. One group of practitioners emphasised AI’s potential to personalise learning, streamline administrative tasks, and support inclusivity. Another group voiced concerns over digital illiteracy, loss of human connection, and ethical issues such as bias and data privacy. A third viewpoint recognised AI as a catalyst for redefining the professional role of FE teachers from content deliverers to facilitators and mentors requiring continuous professional development (CPD) and new pedagogical approaches. Overall, the findings indicate that while AI offers significant potential benefits for FE colleges, its positive impact depends on effective governance, targeted investment in staff training, and curriculum reform that embeds both digital literacy and irreplaceable human skills. This research contributes to the limited evidence base on AI in UK FE by demonstrating how trainers conceptualise its impact and by offering insights to guide institutional strategy, policy development, and teacher education in the sector.